Equity valuation: Greenvolt Energias Renováveis S.A. - Mota, João Carreira Reis Ballester (2022)
This research was developed with the objective of estimating the fair value of Greenvolt shares at 31st December 2021. Also, to understand if at the time the firm was undervalued or overvalued by the market, while comparing the actual market value with the estimated fair value. Greenvolt Energias Renováveis S.A. is a Portuguese company that produces energy from renewable sources, such as forestry biomass, solar and wind. It aims to become one of the main players in the production of renewable energy. In July 2021 it did its Initial Public Offering by listing in the EuroNext Lisbon stock exchange. In this dissertation it was made a valuation on Greenvolt using the Discounted Cash Flows (DCF) applying the Free Cash Flow to the Firm (FCFF) method, and Relative Valuation. The assumptions made are supported by both the firms’ own projections and its historical performance, as well as, an analysis of the macroeconomic environment and industry. The results obtained in the two methodologies used suggest different conclusions. However, the DCF method suggests that the market price Greenvolt was lower than the fair value, at 31st December 2021.